(untitled) (Conferencea, 2023)
This article is due to the importance of studying the semantics of different parts of speech, including prepositions. Their semantics, although much more attention is now being paid to it than before, is still a subject of little research and controversy.And also to determine the lexical meaning of spatial prepositions, this is especially true for derivational processes that take place when modeling the derived meanings of prepositions. Many researchers consider the importance of this problem. But until now, research has been limited to searching for possible meanings of prepositions, describing these meanings.